An Introduction to New Testament Christology - Brown, Raymond E. (Raymond Edward) (New york ; Mahwah Paulist Press, 1994)
Jesus Christ -- Person and offices -- Biblical teaching. Bible. -- New Testament -- Theology. Bible. -- New Testament -- Criticism, interpretation, etc.
Keywords: Time magazine has hailed Raymond Brown as "the leading U.S. Catholic authority on the Bible". Now, in this accessible work written for all Bible students, Brown presents an intelligible introduction to the way Jesus was understood in His lifetime and in the lifetimes of His original followers